1995
DOI: 10.1300/j096v02n02_03
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Health Complaints Associated with Commercial Processing of Mushroom Compost in Southeastern Pennsylvania

Abstract: In response to complaints from local residents, we investigated health effects near a large repository for spent mushroom compost. We administered a symptom questionnaire to people living close to the compost site and to a comparison group farther away. We also surveyed local physicians for their clinical impressions, interviewed providers at a clinic for migrant farm workers, and tested air, water, and compost specimens for pesticide and fertilizer contamination. Respondents living within 3000 feet of the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…A dozen case reports of disease among individuals exposed to compost dust has been published since the 1980s. Six addressed allergic diseases to molds (hypersensitivity pneumonitis) and allergic bronchopulmonary aspergillosis (ABPA), because of Aspergillus fumigatus or actinomycetes (hypersensitivity pneumonitis) (Allmers et al, 2000;Brown et al, 1995;Bünger et al, 2007;Cobb et al, 1995;Kramer et al,1989;Schappler-Scheele, 1999;). One case was organic dust toxic syndrome (ODTS), one case was insufficiently characterized (hypersensitivity pneumonitis or ODTS), one case was external otitis from Aspergillus niger, and three were invasive aspergillosis (Bünger et al, 2007;Clark et al, 1984;Weber et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A dozen case reports of disease among individuals exposed to compost dust has been published since the 1980s. Six addressed allergic diseases to molds (hypersensitivity pneumonitis) and allergic bronchopulmonary aspergillosis (ABPA), because of Aspergillus fumigatus or actinomycetes (hypersensitivity pneumonitis) (Allmers et al, 2000;Brown et al, 1995;Bünger et al, 2007;Cobb et al, 1995;Kramer et al,1989;Schappler-Scheele, 1999;). One case was organic dust toxic syndrome (ODTS), one case was insufficiently characterized (hypersensitivity pneumonitis or ODTS), one case was external otitis from Aspergillus niger, and three were invasive aspergillosis (Bünger et al, 2007;Clark et al, 1984;Weber et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, available epidemiological data are not sufficient to determine whether or not the risk of allergic disease is increased in compost workers, even if some biological marks (IgG antibodies against mold species and actinomycetes) indicated high exposure levels (Beffa et al, 1998;Bünger et al, 2000;Clark et al, 1984;Cobb et al, 1995;Van den Bogart et al, 1993). The incidence rates of allergic disease in compost workers have not been estimated because no properly designed prospective studies have been conducted.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning nearby residents of composting plants, some epidemiological studies have found no relationship between respiratory symptoms and place of residence (Cobb et al, 1995 ), nor with the concentration of Aspergillus fumigatus (Browne et al, 2001 ). Others, in contrast, have shown that residents living within 150–200 m of a composting plant were affected, suffering from irritative respiratory complaints similar to mucous membrane irritation and from excessive tiredness (Herr et al, 2003 ).…”
Section: Impact On Health Of the Exposure To Aerosols Emitted From Comentioning
confidence: 99%
“…If the association between composting bioaerosol exposure and adverse health effects has been demonstrated for compost workers in a small number of cases (Herr et al 2003;Bünger et al 2007), the situation is not so clear concerning nearby residents. Some studies have found no relationship between respiratory symptoms and place of residence (Cobb et al 1995) or with the concentration of Aspergillus fumigatus (Browne et al 2001), while others have shown that residents located within 150-200 m of a composting plant were affected, suffering from irritative respiratory complaints similar to mucous membrane irritation (Herr et al 2003). Therefore, even if it is clear that exposure to some airborne micro-organisms present in composting bioaerosols can lead to human health impacts, the interpretation of air sampling results remains difficult (Marchand et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…2007), the situation is not so clear concerning nearby residents. Some studies have found no relationship between respiratory symptoms and place of residence (Cobb et al. 1995) or with the concentration of Aspergillus fumigatus (Browne et al.…”
Section: Introductionmentioning
confidence: 99%